Perilaku Ekonomi, Monopoli, dan Korupsi: Kajian Sistem Hisbah dalam Perspektif Psikologi Ekonomi Islam - Haris Santoso (Kuras Institute, 2024)
Monopoly and corruption remain major challenges in modern economic governance, particularly in developing countries such as Indonesia. These problems indicate that economic distortions are not merely caused by regulatory weaknesses, but are also rooted in deviant economic behavior, including moral disengagement, abuse of power, and weak ethical internalization among market actors. This study aims to analyze the hisbah system as an Islamic economic supervisory mechanism and examine its relevance in preventing monopoly and corruption from the perspective of Islamic economic psychology. This research employs a qualitative descriptive approach using library research methods. Primary sources consist of classical Islamic scholarly works by Al-Māwardī, Ibn Taimiyah, and Al-Ghazālī, while secondary sources include contemporary studies on monopoly, corruption, and economic supervision. In addition, this study incorporates perspectives from economic psychology to analyze behavioral motivations, ethical decision-making, and the psychological factors influencing economic conduct and market behavior. Data are analyzed through content analysis and comparative analysis to explore the behavioral and psychological dimensions of the hisbah system in relation to modern economic governance. The findings indicate that hisbah functioned not only as a legal and administrative institution, but also as a moral and psychological instrument that shaped ethical economic behavior through preventive supervision, value internalization, and social accountability. In contrast, modern supervisory systems tend to be reactive, fragmented, and predominantly legalistic, often neglecting behavioral aspects. This study concludes that integrating hisbah principles into contemporary economic governance can strengthen efforts to prevent monopoly and corruption by fostering ethical behavior and sustainable economic justice.